Zoom-Based PjBL Learning Model; Its Influence On Student Learning Outcomes In Social Arithmetic Materials - Tristya Dewi Kosmani; Sylvia J. A. Sumarauw; Anekke Pesik (Departement of Mathematics Education, 2023)
This study aims to describe the effect of applying the Project Based Learning Learning Model on learning mathematics on social arithmetic material in schools via Zoom on student learning outcomes. The approach used by researchers is a quantitative approach with a quasi-experimental research type. The research subjects were class VII students of SMP Negeri 1 Modayag, totalling 49 students. The control class consisted of 25 students, and the experimental class consisted of 24 students. The instrument used is a test in the form of multiple-choice questions. The data analysis technique uses the independent sample T-test statistical method. The study results show the influence of applying the PjBL learning model to learning mathematics on the results of learning mathematics on social arithmetic material. The results showed that (1) there was a significant difference in the academic achievement of the control and experimental class students after different treatments, namely the control class 61.80 and the experimental class 79.38. (2) The hypothesis test results show that H0 is rejected, indicating an increase in student learning outcomes after implementing the Zoom-based PjBL model.